Experience of primary care for people with HIV: a mixed-method analysis - Rai,T; Bruton,P; Kall,M; Ma,R; Pufall,E; Day,S; Delpech,V; Ward,H (British Journal of General Practice, 2019)
BackgroundAdvances in treatment have transformed HIV into a long-term condition (LTC), presenting freshchallenges for health services, HIV specialists and general practitioners (GPs).AimTo explore the experience of people living with HIV (PLHIV) regarding using their GPs.Design and settingA mixed-method analysis using data from two sources: a nationally-representative survey of PLHIVand a qualitative study with London-based PLHIV.MethodsUnivariate logistic regression for quantitative data and Framework analysis for qualitative data.ResultsThe survey had 4,422 participants; the qualitative study included 52 participants. In both studies, GPregistration and HIV status disclosure were high. Similar to general population trends, recent GP usewas associated with poor self-rated health status, co-morbidities, older age and lower socioeconomic status. Two-thirds reported a good experience with GPs; a lower proportion feltcomfortable asking HIV-related questions. Actual or perceived HIV stigma were consistentlyassociated with poor satisfaction. In the interviews, participants with additional LTCs valuedsensitive and consistent support from GPs. Some anticipated, and sometimes experienced, problems relating to HIV status, GPs’ limited experience and time to manage their complex needs. Sometimesthey took their own initiatives to facilitate coordination and communication. For PLHIV, a ‘good’ GPoffered continuity and took time to know and accept them without judgement.ConclusionWe suggest clarification of roles and provision of relevant support to build confidence in GPs andprimary care staff to care for PLHIV. As PLHIV population ages, there is a strong need to developtrusting patient/GP relationships and HIV-friendly GP practices.